Promoting Creative Professional Behavior of Future Educators: The Role of Social Capital, Motivation and Self-Efficacy - Ida Nugroho Saputro; Tuatul Mahfud; Ayu Intan Sari; Sukatiman (Интеграция образования, 2023)
Introduction. Creative teaching behaviour for vocational teacher candidates has increased students’ creative skills. So, it is natural for scholars to pay full attention to how to shape creative teaching behaviour for teachers and candidates. Therefore, this study aims to explore the role of social capital on the creative teaching behaviour of teachers by involving motivation and self-efficacy as mediators. Materials and Methods. This study involved university students who were involved in a teacher education program. Two hundred twenty-eight campus students in a teacher education program at a state university in Yogyakarta-Indonesia participated in this study. Structural equation modelling analysis is used to prove the hypothesis. Results. The study results reveal that teacher candidates’ creative teaching behaviour is influenced by social capital, motivation, and self-efficacy. In addition, teacher candidates’ strength of social capital also predicts motivation and beliefs related to their teaching abilities. This study also proves that motivation and self-efficacy act as mediators that significantly mediate the effects of social capital on creative teaching behaviour for teacher candidates. Discussion and Conclusion. The results of this study provide important implications for university lecturers involved in teacher education programs to strengthen social capital, motivation, and self-efficacy for teacher candidates through the teaching process.